The impact of initiating dividend payment on shareholders wealth / Mohd Fauzi Mahmud - Mahmud, Mohd Fauzi (1997)
Following a period of rapid expansion in the last eight years, the Malaysian economy is estimated to expand at a more sustainable pace. Real Gross Domestic Product(GDP) is envisaged to register a slower growth of 8.2% in 1996 compare with 9.5% in 1995.The rates of growth in all sectors expected to moderate from the high levels achieved in 1995. In line with the GDP growth, nominal Gross National Product (GNP) continues to increase to RM 235.3 billion. Per capita income of the population in Malaysia is envisaged to rise to reach RM 11,118. In term of purchasing power parity, the per capita income is equivalent to US$12,508. The moderation in economic growth has been accompanied by a slower growth in consumption, leading to an improvement in national savings as a percentage of GNP. The nation's saving - investment gap is expected to narrow, thereby enabling the nation to reduce its dependence on foreign resources, especially external borrowings to finance the gap. The improvement in the nation's resources position is attributed to the smaller resource gap of the private sector, as more savings are mobilised from individuals to the Employees Provident Fund(EPF) as a result of the higher number of contributors and the recent one percentage point increase in the contribution rate by employees, as well as through the newly established Amanah Saham Wawasan 2020, and the corporate sector as a result of increased earning. Dividend refers to cash distributions of earnings. Generally, any direct payment by the corporation to the shareholders may be considered part of dividend policy.